Production rule system for XML-Relational mapping - Lyamin, Andrei V. (Computer Tools in Education, 2018)
Production rule system is an artificial intelligence method that can be used for XML-relational mapping, which is a nontrivial task. The purpose of the presented study is to develop a production rule system that could be successfully applied for unique mapping XML documents to relational model and back. Analysis of different XML-relational mapping methods used in modern informational systems had been conducted. A unique method of mapping relational data structures to hierarchical ones had been developed based on the production rule system. A mapping example of XML document with information about virtual labs had been described.